Is it possible to evaluate the ecological status of a reservoir using the phytoplankton community? - Vicentin, Aline Martins [UNESP]; Rodrigues, Eduardo Henrique Costa [UNESP]; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo Luiz Martins (FapUNIFESP (SciELO), 2018)
Aim: The present study aims to evaluate the ecological status of the Broa reservoir through the application of the ecological index Evenness E2 on phytoplankton. Methods: Phytoplankton samples from surface were obtained during the dry period (June/2015) in 9 points (P1 to P9), along a longitudinal transect in the reservoir. The qualitative analysis was performed using binocular optical microscope, and the quantitative analysis was performed using the sedimentation chamber method and inverted microscope analysis. The Uniformity Index was calculated on density and richness data. The reference values used in this study were set according to the literature covering 5 classifications (High, Good, Moderate, Low and Bad) for the water quality from Evenness E2 index for phytoplankton, being 1 the maximum value. Results: The values observed ranged from 0.1142 in P1 to 0.1468 in P3, being both classified as “Bad”, since values were less than0.21. Conclusions: The result reinforces the sanitary problem of the reservoir, the occurrence of consecutive algae blooms because the amount of nutrients in the region. A massive occurrence of Cyanobacteria was observed, with emphasis on the species Aphanizomenon gracile, which may be related to the adaptive advantages that this class presents on the community in eutrophic environments. Activities in the basin can contribute effectively to the eutrophication process of the reservoir, such as agriculture, sand mining and livestock. The water quality is compromised due to the dense presence of potentially toxic species, reflects of the eutrophication process, pointing commitments for the multiple uses of the reservoir, as well as human and ecosystem health. These processes could be corroborated by the application of the index and indication of poor water quality.
É possível avaliar o potencial ecológico de um reservatório usando a comunidade fitoplanctônica?
Keywords: Ecological Uniformity Index; Eutrophication; Evenness Index E2; Phytoplankton; Water quality